Multi-Population Optimization Framework Based on Plant Evolutionary Strategy and Its Application to Engineering Design Problems - Cheng, Hongwei; Li, Jun; Zhang, Xiaoming; Li, Tingjuan; Zhang, Panpan (International journal of computational intelligence systems, 2025)
Optimization problems are widespread across various fields, including industry, agriculture, and healthcare. Metaheuristic algorithms (MAs) are commonly employed to solve these problems due to their flexibility and robustness. However, despite their success, MAs inspired by plant evolutionary strategies remain underexplored. This paper introduces a novel multi-population optimization framework based on the plant evolutionary strategy (PES_MPOF), which leverages plant evolutionary principles to improve optimization performance by maintaining population diversity and accelerating convergence in complex tasks. PES_MPOF integrates multiple subpopulations, each evolving according to different plant evolutionary models. These subpopulations mimic natural distribution and reproduction strategies, fostering solution diversity through both cooperation and competition. Additionally, PES_MPOF adapts population parameters based on the evolutionary performance of subpopulations, further enhancing its robustness and efficiency. The PES_MPOF algorithm was tested on the IEEE CEC 2020 benchmark suite and several classic engineering design problems. It outperforms other state-of-the-art optimization algorithms, demonstrating significant improvements in global optimization, solution accuracy, and convergence speed. PES_MPOF effectively addresses the challenges of premature convergence and loss of diversity, making it a robust and efficient optimization tool. Its innovative multi-population framework, inspired by plant evolutionary strategies, enhances both exploration and exploitation. Experimental results validate its effectiveness across a broad range of optimization problems, including those with constraints. The part of algorithm’s code will be made available upon the paper’s acceptance: https://github.com/ChengHongwei430/PES_MPOF .